High glucose promotes podocyte movement: From the perspective of single cell motility assay. (26th January 2023) - Zhang, Junhui; Zhang, Yuping; Zhang, Qiong; Feng, Yanhai; Deng, Xiuyuan; Deng, Fang; Chen, Bing; Hu, Jiongyu
Abstract: Podocytes are highly specialized glomerular epithelial cells that play a crucial role in maintaining the glomerular filtration barrier, impairment of which usually leads to proteinuria. The phenotypic alterations of podocytes are described to be one of the critical mechnisms underlying podocyte detachment from the glomerular basement membrane. High glucose is the major factor mediating the renal damages and podocyte injuries in the process of diabetic nephropathy. It was revealed that high glucose stimulated the epithelial‐to‐mesenchymal transition of podocyte, thus contributing to proteinuria. When the podocytes converse from epithelial phenotype to mesenchymal phenotype, their migratory capacity significantly increases. Previously, cell migration is conventionally detected by the wound healing assay and the transwell assay. In this study, we investigated and comfirmed the possibility of using single cell motility assay for the anaysis of podocyte motility under high glucose condtition.